Bicultural approach to teaching Russian for Slovenians and Slovenian for Russians - Makarova Tominec, Irina (Slavia Centralis, 2021)
This article presents a model of practical implementation of the European guidelines for intercultural language teaching (ICLT) in the context of beginner courses of Russian and Slovenian as a foreign language (level A1, A2) at the University of Primorska in Koper, Slovenia. The purpose of this paper is to show that, unlike the interculturally undefined approach of most textbooks addressing users worldwide, that do not consider the social and cultural specifics of each target environment, the biculturally focused approach shows a number of advantages. The concept introduced is then concretised, both theoretically and content-related, by examining some of the intercultural gaps in the case of Russian-Slovenian contacts identified by online questionnaires for Russian-speaking immigrants in Slovenia and for native Slovenian speakers.
Keywords: intercultural language teaching; intercultural pragmatics; Russian; Slovenian as a foreign language; speech etiquette; Russian-Slovenian contacts